World Bank Client Satisfaction Study, Pakistan 2013 : Executive Summary - Gallup Pakistan (World Bank, Washington, DC, 2014)
The World Bank conducted a Client Satisfaction Study (CSS) for Pakistan in 2013 to identify the client's perception of Bank's role and presence in the country. This paper includes the following sections: overall attitude towards World Bank in Pakistan; views on country partnership strategy; views and opinion about services of World Bank; World Bank access and media habits: advisory for a future strategy; and detailed views about World Bank from client side.